Development of Duckweed (Lemna minor)-Based Cracker with Enhanced Protein and Fibre Content (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
With the global shift towards health and sustainability, this study explores the potential of duckweed (Lemna minor) as a novel ingredient in high-protein, high-fibre crackers. Known for its rapid growth and rich nutritional profile, duckweed offers a promising solution to the rising demand for sustainable, plant-based proteins. This research evaluates the physicochemical properties of duckweed powder (DP), its incorporation at varying concentrations (2%, 4%, and 6%), and its impact on cracker quality. Key findings reveal that DP significantly enhances protein and fibre content without compromising sensory attributes. Crackers with DP exhibit improved moisture retention and shelf life, supporting their viability in health-oriented snacks. Proximate analysis shows DP had a remarkable amount of fibre (36.07%) and carbohydrates (52.43%). Incorporating DP increases moisture, protein, ash, crude fibre, and total dietary fibre in crackers. Functional properties, including water-holding (5.33 g/g) and oil-binding capacity (5.08 g/g), further highlight its benefits in food formulations. Sensory evaluation confirms that crackers with up to 6% DP maintain acceptable taste, texture, and overall appeal, with the 2% formulation receiving the highest acceptability score. This study underscores the potential of duckweed as a sustainable and nutritious food ingredient, offering an alternative protein source for the industry.
Keywords: Duckweed; Aquatic plant; Plant-based proteins; Healthy snack; Fibre